Computational study on 2,6-diamino-3,5-dinitropyrazine and its 1-oxide and 1,4-dioxide derivatives - Gökçınar, Elif; Klapötkea, Thomas M.; Bellamy, Anthony J. (Elsevier, 2010)
The enthalpies of formation for 2,6-diamino-3,5-dinitropyrazine (I), 2,6-diamino-3,5-dinitropyrazine 1-oxide (II) and 2,6-diamino-3,5-dinitropyrazine 1,4-dioxide (III) were calculated using the complete basis set (CBS-4M) method of Petersson and coworkers in order to obtain very accurate energies and compared with experimental values that were available for I and II. I was identified as the most stable compound, both thermodynamically (least endothermic) and with respect to its impact sensitivity. This is in good agreement with the experimental findings. The detonation parameters for all species were calculated using the EXPLO5 code. 2,6-Diamino-3,5-dinitropyrazine 1,4-dioxide (III) has been identified to be a promising nitrogen-rich explosive which exceeds the explosive power of II and its performance is comparable or slightly superior to that of RDX.
Keywords: Explosives; N-oxides; CBS-4M; RDX replacements; Electrostatic potentials